SCHOOL PRINCIPAL LEADERSHIP AT SMK NEGERI 3 AMUNTAI, HULU SUNGAI UTARA REGENCY - Barkatullah, Barkatullah; Berkatillah , Akhmad; Rahmayanti, Anita (International Journal Multidisciplinary (IJMI), 2025)
Objective: This study aims to analyze the leadership practices of the principal at SMK Negeri 3 Amuntai, Hulu Sungai Utara District, particularly in relation to organizational effectiveness, teacher discipline, motivation, and the achievement of school goals. Method: The research employed a qualitative approach, with data collected through observation, in-depth interviews, and documentation. Informants were selected using snowball sampling, involving 12 participants consisting of school leaders and teachers. Data analysis followed three stages: data condensation, data display, and conclusion drawing/verification to ensure analytical rigor and credibility. Results: The findings indicate that the principal’s leadership is generally adequate across nine key indicators, including the ability to mobilize subordinates, decision-making, material considerations, participatory decision-making, implementation of decisions, delegation of authority, briefing, guidance, and supervision. However, weaknesses were identified in communication and coordination between the principal and subordinates, largely due to the principal’s limited presence at school and external commitments. Constraining factors include insufficient discipline and limited funding, while supporting factors involve the principal’s ability to direct, guide, and implement decisions effectively. Novelty: This study contributes by highlighting the critical role of communication and coordination as determining factors in the effectiveness of school leadership within vocational education contexts, offering practical insights for leadership improvement.